ADSORPTION OF PHENOLS FROM OLIVE OIL MILL WASTEWATER AS WELL AS N AND P FROM A SIMULATED CITY WASTEWATER LIQUID ON ACTIVATED GREEK LIGNITES - Papanicolaou, C.; Triantafyllou, G.; Pasadakis Ν.; Foscolos Α,Ε. (Bulletin of the Geological Society of Greece, 2010)
The results show that surface area of activated coal samples increased substantially and in some more than the commercial one. The increase in surface area was higher the higher the carbon content and the lower the ash content. The adsorption capacity of phenols and the decrease of COD (Chemical Oxygen Demand) in olive oil mil wastewater disposals were measured in selected samples as well as the decrease of COD and the adsorption of nitrogen and phosphorus from a solution which simulates city waste disposals were measured in 14 selected Greek lignites and 1 commercially available activated lignite sample (HOK). The maximum recorded adsorption of phenol was 30.6 mg/g of activated lignite while the commercial one (HOK) adsorbed 16 mg/g of activated lignite. The COD reduction was 1262 mg of COD/g of activated lignite while in the commercial one the reduction was 439 mg of COD/g of activated lignite. The maximum adsorption of N and P from the simulated city waste liquid was 6.41 mg/g of activated lignite and 2.52 mg/g of activated lignite, respectively. while the commercial one (HOK) adsorbed 2.84 mg/g and 2.42 mg/g, respectively. Finally, the COD reduction was 50.28 mg/g of activatedlignite and 34.92 mg/g for the commercially one (HOK). The results show that Greek activated lignites can be used successfully for cleaning industrial and city wastes. These findings open the door for the economic exploitation of small to medium size lignite deposits in Greece, which are widespread in Greece.